(untitled) - Auli-Maarit Haikonen; Mervi Roos; Meeri Koivula; Kristi Rannus; Tarja Suominen; Merja Harmoinen (University of Ostrava, 2023)
Aim: The aim of this study was to explore the implementation of appreciative management from the perspective of healthcare workers in selected Estonian healthcare organizations. Design: The study was conducted as a cross-sectional study. Methods: Data were collected from healthcare workers (n = 215) using an Appreciative Management Scale in two different sized hospitals and two healthcare centers. Data were analyzed using non-parametric tests. The study was reported according to STROBE guidelines. Results: Appreciative management was implemented very well. Of the dimensions of appreciative management, equality of employees was the best implemented and systematic management was the least well implemented. Appreciative management had a statistically significant connection with intention to change workplace and with experience of appreciation from first-line managers and upper managers. Conclusion: With the help of appreciative management, it may be possible to increase commitment to work. The appreciation offered by managers to healthcare workers seems to improve healthcare workers' evaluation of the implementation of appreciative management. In health care, it is important to recognize appreciative management and the benefits it creates for healthcare workers' commitment to their work and profession.